Compósitos NiO-CGO obtidos pelo método de síntese em uma etapa - Grilo, João Paulo de Freitas (2015)
Composite NiO-C0.9Gd0.1O1.95 (NiO-GDC), one of the materials most used for the manufacture of anodes of Cells Solid Oxide Fuel (SOFC) currently, were obtained by a chemical route which consists in mixing the precursor solution of NiO and CGO phases obtained previously by the Pechini method. The nanopowders as-obtained were characterized by thermal analysis techniques (thermogravimetry and Differential Scanning Calorimetry) and calcined materials were evaluated by X-ray diffraction (XRD). Samples sintered between 1400 and 1500 ° C for 4 h were characterized by Archimedes method. The effects of the composition on the microstructure and electrical properties (conductivity and activation energy) of the composites sintered at 1500 ° C were investigated by electron microscopy and impedance spectroscopy (between 300 and 650 ° C in air). The refinement of the XRD data indicated that the powders are ultrafine and the crystallite size of the CGO phase decreases with increasing content of NiO. Similarly, the crystallite of the NiO phase tends to decrease with increasing concentration of CGO, especially above 50 wt % CGO. Analysis by Archimedes shows a variation in relative density due to the NiO content. Densities above 95% were obtained in samples containing from 50 wt % NiO and sintered between 1450 and 1500 °C. The results of microscopy and impedance spectroscopy indicate that from 30-40 wt.% NiO there is an increase in the number of contacts NiO - NiO, activating the electronic conduction mechanism which governs the process of conducting at low temperatures (300 - 500 °C). On the other hand, with increasing the measuring temperature the mobility of oxygen vacancies becomes larger than that of the electronic holes of NiO, as a result, the high temperature conductivity (500-650 ° C) in composites containing up to 30-40 wt.% of NiO is lower than that of CGO. Variations in activation energy confirm change of conduction mechanism with the increase of the NiO content. The composite containing 50 wt. % of each phase shows conductivity of 19 mS/cm at 650 °C (slightly higher than 13 mS/cm found for CGO) and activation energy of 0.49 eV.